2002
DOI: 10.1519/1533-4287(2002)016<0433:srotts>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Selective Recruitment of the Triceps Surae Muscles With Changes in Knee Angle

Abstract: The muscles of the triceps surae group are important for performance in most sports and in the performance of activities of daily life. In addition, hypertrophy and balance among these muscles are integral to success in bodybuilding. The purpose of this study was to compare the muscle utilization patterns of the 2 major muscles of the triceps surae group, the soleus (SOL) and gastrocnemius (lateral head = LG and medial head = MG), and the tibialis anterior (TA) as an antagonist muscle to the group. Their elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 13 publications
5
20
1
1
Order By: Relevance
“…Triceps surae REX as the knee maintains full extension, as done in the current study, note similar results (17,(23)(24)(25). Plantar flexion at three angles (0, 30, and 60Њ) and velocities (6,30, and 60Њ·s Ϫ1 ) showed peak MG IEMG values were significantly greater with full (0Њ) knee extension (24).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Triceps surae REX as the knee maintains full extension, as done in the current study, note similar results (17,(23)(24)(25). Plantar flexion at three angles (0, 30, and 60Њ) and velocities (6,30, and 60Њ·s Ϫ1 ) showed peak MG IEMG values were significantly greater with full (0Њ) knee extension (24).…”
Section: Discussionsupporting
confidence: 86%
“…At loads 5-10% of the subject's maximal voluntary contraction, the same study showed significantly higher peak MG IEMG values occurred at a shortening velocity of 60Њ vs. 6Њ·s Ϫ1 as full knee extension was maintained (24). Triceps surae activity during isotonic plantar flexion with full knee extension noted MG IEMG activity was significantly greater than for the SOL (23). MG activity from a 60-second jump test led to greater IEMG and fatigue during concentric, eccentric, and pre-activation phases vs. the SOL (17).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The knee angle utilized for each mode of testing was different with the knee angle being 0 rad for the 3RM and 2.09 rad for isokinetic testing. It is known that selective recruitment of the triceps surae muscles can occur through the manipulation of knee angles (23, 40). Additionally, isolation of the plantar flexors during isokinetic testing has previously been known to be difficult.…”
Section: Discussionmentioning
confidence: 99%